Cervical Length at Mid-gestation in Screening for Preterm Birth in Twin Pregnancy. Issue 11 (November 2016) - Pagani, G.; Stagnati, V.; Fichera, A.; Prefumo, F.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2016;48:56–60) Preterm birth (PTB) is a leading cause of neonatal morbidity and mortality, and the increased proportion of twin births is one factor that contributes to PTB. A short cervical length (CL) in midgestation is one among the various risk factors that is considered predictive for spontaneous PTB of less than 32 weeks in twin gestations.